Transformation of Sufistic Da'wah and Islamic Psychotherapy Through Online Manaqib: A Qualitative Case Study on Tarekat Qadiriyah Naqsyabandiyah Community in Indonesia - Rahman Hakim, Budi (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
This study explores the transformation of Sufistic da'wah and Islamic spiritual psychotherapy through the practice of online manaqib in the Qadiriyah Naqsyabandiyah (TQN) Tarekat community in Indonesia. This adaptation emerged in response to geographical and time constraints in traditional spiritual gatherings. Through semi-structured interviews, participatory observations, and digital documentation analysis, this study analyzes the spiritual and therapeutic impact of online manaqib. The results demonstrate that this practice upholds the core values of Sufi spirituality while expanding the reach of da'wah through digital platforms, such as Zoom. Virtual interaction between the murshid and the disciple fosters a meaningful spiritual connection, even in the absence of physical presence. Additionally, online manaqib serve as a therapeutic medium that promotes inner peace and spiritual resilience. This study presents an integrative model for technology-based spiritual guidance services, which is particularly relevant for urban communities in the digital and post-pandemic era. Keywords: manaqib online, religious counseling, digital spiritual community, islamic psychotherapy, neo-sufism